A116 ABERRANT IMMUNE RESPONSE AGAINST INVADING BACTERIA INCREASES MORTALITY IN MUC2 MUCIN DEFICIENT MICE IN LPS INDUCED SEPSIS. (1st March 2018) - Kumar, M; Moreau, F; Chadee, K
Abstract: Background: A physical barrier in the gut, formed mainly by the mucus bilayer, keeps gut microbiota and/or components away from translocating into host tissues. Perturbation of the mucus layer, as in inflammatory bowel diseases (IBD), leads microbial penetrants to initiate local and systemic inflammation. Unregulated inflammation can aggravate into sepsis, causing mortality due to multiple organ failure. IBD patients are at high risk for developing sepsis due to their defective gut barrier function, yet is poorly understood. Muc2 -/- mice without a mucus barrier have low-grade inflammation with bacterial penetrants and is an excellent model to study chronic colitis and ideal for IBD related studies. Aims: To assess immune response in Muc2 -/ - mice in lipopolysaccharide (LPS) induced sepsis. Methods: LPS was administered in Muc2 -/- and WT littermates intra-peritoneally (i.p.) as 5mg/kg body weight (BW) and monitored for BW loss and mortality. Mice were euthanized at 24 or 48 h. Spleen and intestinal tissue were harvested for immunophenotyping and histology. Single cell suspension of splenocytes were prepared and stained with anti CD3, CD4, CD8, CD19 and CD49b antibodies for T-cells, B-cells and NK cells. Apoptotic and dead cells were determined by Annexin V and 7-AAD staining. Immunophenotyping was done using FACS Canto and data was analyzed by FlowJo software. Bacterial penetrance into distal ileum, cecum and colonic tissue was determined using fluorescence in situ hybridization (FISH) and real time RT-PCR. Results: Muc2 -/ - mice basally exhibited significantly larger numbers of splenic B-cells, CD8+ cells and NK cells than WT littermates suggesting ongoing elevated systemic inflammation. CD4+ cells were unchanged. Notably, Muc2 -/- mice exhibited increased apoptosis of splenic B-cells at baseline indicating systemic inflammation and immunosuppression. Following LPS induced sepsis, we observed increased bacterial penetrance through the distal ileum, cecum and colonic walls of Muc2 -/- mice at 24 and 48 h as compared to WT littermates. In WT littermates, LPS treatment led to massive accumulation and secretion of mucus (mucus plug) in the lumen that impaired bacterial translocation. Moreover, splenocytes in LPS induced sepsis showed significantly increased apoptosis of B-cells, decreased apoptosis of CD4+ and CD8+ cells in Muc2 -/- as compared to WT littermates. The aberrant immune response in Muc2 -/- mice was correlated with significantly increased bacterial burden in the liver and spleen resulting in rapid BW loss and mortality. Conclusions: Our research suggests that during chronic IBD, host immune cells may become exhausted with continual exposure to microbial penetrants leaking through the altered and/or depleted intestinal mucus barrier. This can result in aberrant immune response against invading pathogens and increased susceptibility to sepsis. Funding Agencies: CCC, CIHR